Preliminary investigation of anti-fungal activity of crude root extract of makahiya (mimosa pudica). - Moralba, Marian Argie Ramos
Standard aqueous extract from Mimosa pudica roots was made by creating a 1:2 weight to volume ratio. Four (4) concentrations (25, 50, 75, 100) were made from the standard aqueous solution in order to test the effectivity of the extract against three species of fungal dermatophytes namely: Microsporum canis, Trichophyton rubrum and Trichophyton tonsurans. The aqueous extract was found to completely inhibit the growth of T. tonsurans but only slowed down the growth of M. canis and T. rubrum at 25) were made from the standard aqueous solution in order to test the effectivity of the extract against three species of fungal dermatophytes namely: Microsporum canis, Trichophyton rubrum and Trichophyton tonsurans. The aqueous extract was found to completely inhibit the growth of T. tonsurans but only slowed down the growth of M. canis and T. rubrum at 25 concentration of crude extract. Among the three dermatophytes, M. canis was the most resistant while T. rubrum was the most susceptible or sensitive to the M. pudica roots extract.